Incidências do sujeito do inconscienete em produções escritas de crianças - Soares, Mércia Irabel (2013)
This dissertation focuses on text production for children, it is linked to the class project named: subject of unconscious, discussion and social insertion in learning situations and language disorder, it follows the methodical criteria used by the class project a bready made above. The goal of this research is drawing the attention of teachers to the writing of children, not only to the cognitive aspects, genially cited by most of theorist, whose, theories support pedagogic work in classrooms. So this class of research turns to researches on linguistic and psychoanalysis, known concepts of Freud and Lacan. Then, its general goal: investigate the subjective incidences of children s glasswork, larine how to write, considering the fart between the subject of unconscious and the working of language in writing. The specific goals consist of investigation the functioning of the language, that is, the metaphorical and metonymic processes, and investigate formations of unconscious whose signs mark the text. As forgetting words, bad diction, so it was developed and a activity of producing texts with children, both genders, between seven and length years, students of the second grade of the first cycle in public schools, in the city of Recife, the criteria of analysis were guild by principles and concept form Linguistics, specially Saussure and Jakobson and psychoanalysis of Freud and Lacan. The results have shown now the production of texts and to do with facts of structural functioning formation that leaves clue in the text.